Model Bisnis Kanvas Dan Strategi Pengembangan UD Mahakarya Farm Banyuwangi - Nurul Aqila Maulidiya; Sefri Ton; Maghfirotul Amaniyah; Dani Agung Wicaksono; Anis Usfah Prastujati (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Poultry farming businesses such as UD Mahakarya Farm always have internal and external problems, so the desire to develop the business has not been achieved. UD Mahakarya Farm needs to do creative and innovative things with its business models. The purpose of this research is to determine the business model canvas and business strategy. Research methods using qualitative and quantitative. The results of the research show that business development with the Business Model Canvas is still using conventional models. The results of the SWOT analysis showed an IFAS value of 2.95 and an EFAS value of 3.12. In the SWOT analysis, there are eight alternative strategies that can be recommended for business development at UD. Mahakarya Farm.